(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The use of pragmatic strategies into English language training is necessary in order to cultivate communicative competence among students. The ability to effectively use language in a variety of social contexts will be facilitated for learners as a result of this. The purpose of this study is to examine the effectiveness of various teaching approaches that are based on pragmatic tactics in terms of assisting students in dealing with circumstances that they would encounter in real life. The research compares and contrasts traditional methods of teaching language, such as direct and grammar-translation instruction, with more modern methods, such as communicative and task-based language education, in order to investigate the impact on pragmatic competence. With a special emphasis on social norms, politeness tactics, conversational implicature, and speech acts, this study relies on a broad body of literature and empirical research to demonstrate how both explicit and implicit education may assist students in becoming more pragmatically aware. Specifically, the study focusses on how students may become more aware of social norms. Exposure to real conversation and contextualised interaction are examples of implicit tactics that might lead to more organic learning over time. While metapragmatic awareness-raising and direct feedback are examples of explicit teaching that may speed up pragmatic development, examples of implicit approaches include exposure to genuine conversation and contextualised interaction.